Role of Microbes and their Enzymes in Biodegradation of Plastic Waste - Saritha, B.; Remadevi, O. K. (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The sustainable use of synthetic polymers is one of the major challenges of the twenty first century. In the last 150 years the polymers of plastic with various properties have been developed to replace materials such as metal, glass and wood for various applications. Plastic is non-reactive and non-degradable. Hence, there has been an exponential increase in plastic waste generation. Plastic wastes have adversely affected life on earth, due to their undesirable accumulation in landfills, leaching into the soil, increased greenhouse gas emission, etc. Plastic accumulation is the vital cause of environmental pollution and is the ever increasing ecological threat. The methods currently available for eliminating the plastic waste viz., incineration, landfilling, and recycling places more burden on the environment. Hence, the recent focus has been made on the potential of biological systems to degrade synthetic plastics. Microorganisms have been shown to utilise these polymers and convert them into environmentally friendly carbon compounds. The current understanding of the biochemical roles played by microorganisms in enhancing the degradation of synthetic plastics is reviewed.